2004
DOI: 10.1023/b:jarg.0000042008.83699.cc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maturation, Fertilization, Development, and Gene Expression of Mouse Oocytes Grown In Vitro and In Vivo

Abstract: These results showed that in vitro grown oocytes did not have the same developmental capacity as in vivo grown oocytes. We assume that the aberrant expression of maternal-derived genes in the in vitro grown oocytes may cause the poor embryo viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
5
27
1
Order By: Relevance
“…It has been reported that the expressions of growth differentiation factor-9 (GDF-9) and insulin-like growth factor II (IGF-II) are higher in vivo matured oocytes than in vitro matured oocytes [36]. Our results showed that not only GPER was expressed on oocyte Fig.…”
Section: Discussionmentioning
confidence: 46%
“…It has been reported that the expressions of growth differentiation factor-9 (GDF-9) and insulin-like growth factor II (IGF-II) are higher in vivo matured oocytes than in vitro matured oocytes [36]. Our results showed that not only GPER was expressed on oocyte Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Given the fact that competence of oocytes obtained with in vitro techniques is as yet suboptimal when compared to oocytes grown and matured in vivo [3,[5][6][7][8][9], the development of more appropriate in vitro conditions is a prerequisite for obtaining large numbers of competent oocytes in a reproducible manner.…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons include suboptimal IVM conditions as well as genetic and epigenetic characteristics of oocytes themselves. In many human and animal 6 to 8-cell IVM embryos, genome activation does not take place (Kim et al 2004;Schramm et al, 2003). This hindered embryo development is thought to be a consequence of disturbed cytoplasmic maturation or asyncronicity between the cytoplasmic and nuclear maturation in the oocyte.…”
Section: Ivm Methodsmentioning
confidence: 99%
“…Reasons for development stagnation could be manifold, ranging from cytoplasmic immaturity and meiotic spindle formation abnormalities (Combelles et al, 2003;Eichenlaub-Ritter et al, 1988;Miyara et al, 2003;Mrazek & Fulka, 2003;Neal et al, 2002;Pickering et al, 1988) to chromatin fragmentation followed by the appearance of micronuclei (Junk et al, 2002). Also, the in vitro cultivation conditions can be sub-optimal (Chian and Tan, 2002;Junk et al, 2002;Trounson et al, 2001) or the intrinsic factors such as abnormal cell cycle control or affected gene regulation can impede proper oocyte development (Combelles et al, 2003;Eichenlaub-Ritter & Peschke, 2002;Kim et al, 2004). For all those reasons, the safe routine clinical use of IVM oocytes is still under debate, since the quality of such oocytes seems low.…”
Section: Ivm Methodsmentioning
confidence: 99%
See 1 more Smart Citation